Development of Interactive Learning Media with Wordwall to Enhance Student Interest and Understanding in Class X Geography - Harahap, Robby Risky; Rahmadi, Muhammad Taufik; Sugiharto, Sugiharto; Damanik, Muhammad Ridha Syafii (JPG (Jurnal Pendidikan Geografi), 2025)
This research aims to develop wordwall-based learning media and determine students' learning interests and determine students' understanding of remote sensing material. The research subjects were 33 class X 3 students. The research method used is Research and Development (R&D) with reference to the simplified Borg & Gall steps. The research instrument was validated through material experts and media experts to ensure content validity. The research results show that Wordwall-based learning media makes a positive contribution to students' interest in learning. This is shown by an increase in students' comprehension scores after using the media. Apart from that, students' interest in learning about remote sensing material is in the good category, namely high interest. The research results show that Wordwall-based learning media is suitable for use as an alternative innovation in the geography learning process. The conclusion of this research is that Wordwall-based learning media is effective in increasing students' interest and understanding of remote sensing material. This media can be a reference for teachers to create more interactive and interesting learning. This research also recommends further development to integrate other digital learning media in the teaching and learning process.